Distinct Swimming Behavioral Phenotypes Following Serotonin and Dopamine Transporter Modulation in the Adult Zebrafish Novel Tank Diving Test (NTT) - (:unkn) unknown (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background/Objective: Serotonin and dopamine are key neurotransmitters involved in regulating mood, anxiety, and locomotor activity. Specific transporters mediate their reuptake, SERT and DAT, making them targets for drugs such as Fluoxetine and Methylphenidate. Zebrafish (Danio rerio), due to their genetic and neurochemical similarity to humans, serve as a valuable model for studying the behavioral effects of these drugs. This study aimed to compare the behavioral phenotypes induced by SERT and DAT blockers in adult zebrafish using the Novel Tank Diving Test (NTT), thereby generating a swimming profile for drugs acting on these monoamine transporters that can be utilized in drug discovery and behavior. Methods: Adult zebrafish were administered Fluoxetine or Methylphenidate and subjected to the NTT. Behavioral endpoints measured included bottom-dwelling time (anxiety-like behavior), swimming velocity (locomotor activity), and transitions to the upper zone (exploratory behavior). Results: Fluoxetine treatment significantly reduced bottom-dwelling behavior, increased transitions to the upper zone, and decreased erratic swimming, indicating reduced anxiety and enhanced exploration. In contrast, Methylphenidate administration led to prolonged bottom-dwelling and reduced exploration, suggesting increased anxiety-like behavior and decreased exploration. These findings highlight distinct behavioral profiles resulting from selective modulation of serotonergic and dopaminergic pathways. Conclusions: The study demonstrates that SERT and DAT blockades produce divergent behavioral effects in adult zebrafish, with Fluoxetine exhibiting anxiolytic and exploratory-promoting actions. At the same time, Methylphenidate induces anxiety-like and less exploratory behaviors. These results underscore the utility of zebrafish as a valuable translational model for neuropharmacological research and drug discovery, providing insights into the differential impact of serotonergic and dopaminergic modulation on behavior.